The Urgency of the Halal Industry in Light of Islamic Legal Philosophy - Irfan, M. Nurul; Rosyid, Maskur; Marjuni, Kamaluddin Nurdin; Mashilal (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
The Indonesian government, regulators, and Muslim consumers increasingly recognize the halal industry as an essential sector for economic growth. This study aims to assess the understanding, acceptance, and implementation of halal among educated Muslim youth and analyse the urgency of halal in food, tourism, and banking. The research was conducted at four State Islamic Universities (PTKIN) in Central Java, Indonesia, involving 145 students as respondents. A descriptive quantitative approach was applied using structured questionnaires, analysed with frequency and percentage techniques, and interpreted through Islamic legal philosophy, particularly fiqh and maqāṣid al-sharī‘a. The study finds that the halal of food, tourism, economy, and banking has a strong epistemological basis in Islam; however, a segment of Muslim minority students demonstrates rejection or inconsistent implementation due to differences in interpretation, limited accessibility, and perceptions of government policies. Despite this, there is strong support for halal, with over 91% endorsing government initiatives and 92% acknowledging their contribution to economic growth. Based on these findings, the study recommends standardizing halal concepts across sectors, systematically evaluating program impacts, and continuously educating the public to optimise the implementation of Indonesia’s halal industry policy.